(3GdJMQjGJ cCSGS dGUOGQ bQGQGJ GdVHW GdGOGQi hGdQbGHI GdbVGFjI YdjgG (B/ s - (3GTQa GHQGgje eUWai SdjeGfs; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JQLY GgejI GdQSGdI Gdi Gf GdJMQjGJ gi GdSfO GdPi JYeO Gdjg GLgRI GdVHW ai GdeLJeY ddeMGaXI Ydi GdMjGI GdYGeI ai GWGQ ef GMJQGe GdMbhb(B.(3JQLY UYhHI GdOQGSI ai GfgG JHMK Yf fbWI JhGRf Hjf GdGLQGA GdGOGQi hQbGHI GdbVGA Ydjg eY UYhHI GSJNdGU QDjI eMOOI ddJMQjGJ GdGOGQjI hGdJaQbI HjfgG hHjf GdJMQjGJ GdaVGFjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B349-360s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdJMQjGJs; (3GdQbGHI GdaVGFjIs; (3GdVHW GdGOGQis; (3eQGbHI GdeMGOKGJ s; (3hVY GdGLGfH aj eUQs; (3GdXQha GdGSJKfGFjI s; (3GdLQjeI GdGQgGHjI s; (3GdGYJbGd GdGOGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes